Pengenalan Pasar Modal - Hasnita, Novia Tri; Wahyuni, Dian; Norbaida, Norbaida; Ariska, Siti; Hendra K, Joni (CV. Rayyan Dwi Bharata, 2024)
This study aims to identify the character of Acehnese entrepreneurs and the model of introducing capital markets that are right for entrepreneurs. This study was analyzed using a quantitative descriptive approach. The research sample consisted of Aceh Taxable Personable Entrepreneurs, Aceh representative stock exchange leaders, exchange gallery managers, and lecturers who took care of investment courses. The research data was collected using questionnaires, interviews, and discussions. The results of the study show that Acehnese entrepreneurs are risk averse and consider Sharia principles in choosing the type of investment. The right model for introducing capital markets was introduced involving capital markets, local governments, securities companies, educational institutions, and the National Sharia Council of the Indonesian Ulama Council. The right capital market introduced for Acehnese entrepreneurs is the Islamic capital market.